Mikro-habitat ikan pelangi endemik Melanotaenia arfakensis dan implikasinya bagi konservasi insitu di Kebar, Papua Barat Daya - Yemima Kaliele, Mariance; Bawole, Roni; Manangkalangi, Emmanuel; Tebaiy, Selvi; Toha, Abdul Hamid A.; Alfarani Bawole, Christover; Boli, Paulus; Mudjirahayu (Cassowary, 2025)
ABSTRACT: This study examines the microhabitat characteristics of the endemic rainbowfish Melanotaenia arfakensis in two major rivers of Tambrauw, Southwest Papua—Api River and Asiti River—focusing on the spatial dynamics of environmental parameters from upstream to downstream. Results indicate that water temperature, dissolved oxygen (DO), depth, current velocity, and river width show significant spatial trends and directly influence the survival of M. arfakensis. The upstream zones, characterized by lower temperatures (23–26°C), high DO levels (>7 mg/L), moderate current, and stable depth, are identified as optimal habitats and conservation priorities. In contrast, the midstream and downstream zones exhibit gradual habitat degradation, including temperature increases up to 29.1°C and decreased DO levels, approaching the physiological tolerance limits of the species. This decline in microhabitat quality correlates with riparian vegetation loss and anthropogenic pressures. Therefore, an effective in situ conservation strategy must be spatially explicit, adaptive, and participatory—emphasizing thermal refugia protection in the upstream zones, ecological restoration in the midstream, and integrated watershed management with community involvement in the downstream areas. Longitudinal connectivity and the integrity of the entire riverine ecosystem are essential for ensuring the long-term viability of this endemic species.